Exploring Salinity Tolerance in Three Halophytic Plants: Physiological and Biochemical Responses to Agronomic Management in a Half-Strength Seawater Aquaponics System - Ayenia Carolina Rosales-Nieblas; Mina Yamada; Bernardo Murillo-Amador; Satoshi Yamada (Horticulturae)
Understanding halophyte responses to agronomic management in saline environments is crucial for optimizing their cultivation. This study assessed the physiological and biochemical responses of three halophytic species, ice plant (Mesembryanthemum crystallinum L.), romeritos (Suaeda edulis Flores Olv. and Noguez), and sea asparagus (Salicornia europaea L.) cultivated in half-strength seawater aquaponics (approximately 250 mM NaCl) under the following rooting media treatments: (C) untreated rearing water (RW), (pH) pH-adjusted to 5.5 RW, (pH+S) pH-adjusted to 5.5 RW with nutrient supplementation, and (NS) standard nutrient solution + 5 mM NaCl. Salinity was the primary factor influencing plant responses, while agronomic management played a secondary role. Ice plants exhibited stable growth across treatments due to their strong succulence, high water content, and antioxidative system, requiring minimal management, though optimal pH may enhance nutrient availability. Romeritos showed high treatment variability yet maintained biomass production via Na+ compartmentalization, with C treatment supporting better osmotic regulation, while pH adjustments and mineral supplementation induced stress under HSW. Sea asparagus sustained growth across all treatments, likely due to effective K+ retention and osmoregulation, reducing the need for additional management. These findings highlight species-specific salinity tolerance mechanisms and suggest that minimal agronomic management can effectively support halophyte cultivation in saline aquaponic systems.